2014
DOI: 10.1097/01.sa.0000443871.68248.a3
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Endothelial Dysfunction and Acute Brain Dysfunction During Critical Illness

Abstract: Background-Acute brain dysfunction (delirium and coma) during critical illness is prevalent and costly, but the pathophysiology remains unclear. The relationship of acute brain dysfunction with endothelial function, which is impaired in critical illness and may contribute to alterations in cerebral blood flow and blood-brain barrier permeability, has not been studied. We sought to determine whether systemic endothelial dysfunction is associated with acute brain dysfunction during critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
(36 reference statements)
0
25
0
2
Order By: Relevance
“…These data suggest that the inhibition of iNOS-related nitrative stress may attribute to the protective effects of resveratrol against endotoxemia-associated adrenal insufficiency. Endothelial dysfunction, edema, hyperemia and hemorrhage are key characteristics associated with severe inflammation-associated injuries in a variety of organs including lung [38], liver [39], kidney [39] and brain [40]. The adrenal gland is a highly vascularized organ.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the inhibition of iNOS-related nitrative stress may attribute to the protective effects of resveratrol against endotoxemia-associated adrenal insufficiency. Endothelial dysfunction, edema, hyperemia and hemorrhage are key characteristics associated with severe inflammation-associated injuries in a variety of organs including lung [38], liver [39], kidney [39] and brain [40]. The adrenal gland is a highly vascularized organ.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is possible that reductions in perfusion also are associated with underlying cardiovascular disease and/or endothelial dysfunction, which have been associated with both a prolonged neuroinflammatory response and increased blood-brain barrier permeability (36)(37)(38)(39). Reduced cerebral perfusion may also increase the risk of cerebral metabolic dysfunction, which has been shown to worsen following coronary artery bypass graft and correspond to changes in postoperative cognitive performance (35) or increase postoperative neuroinflammation (40)(41)(42).…”
Section: Original Researchmentioning
confidence: 99%
“…47 Healthy volunteers injected with endotoxin had decreased cerebral blood flow, and this was associated with peak serum concentrations of TNF-a. 48 Recently, it was demonstrated that patients with lower vascular reactivity had increased duration of brain dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…48 Recently, it was demonstrated that patients with lower vascular reactivity had increased duration of brain dysfunction. 47 The mechanisms behind endothelial dysfunction and acute brain dysfunction remain unclear, but inflammation could drive structural and functional alterations in the BBB, increasing microvascular permeability and impairing microcirculatory blood flow. [49][50][51][52] These alterations could be secondary to a decrease in the activity of endothelial nitric oxide synthase induced by inflammation 53 or to alterations in the coagulation system, resulting in microthromboses and microinfarcts.…”
Section: Introductionmentioning
confidence: 99%